Educational responses to socioeconomic inequality - Bures, Laura (My University, 2019)
Socioeconomic inequality continues to be a major concern both internationally and within Canada. Educational outcomes for children are one of the key areas affected by this reality. Schools are considered institutions responsible for promoting the social mobility of children. However, due to increasing social, political, and economic disparities among families, schools have redesigned themselves to ensure this idea persists. This paper examines how parental inconsistencies, lack of supportive home environments, and financial burdens associated with low socioeconomic status families have a negative influence on children’s educational outcomes. It investigates why schools have become concerned with implementing programs to help alleviate the effects of socioeconomic inequalities on children and their families. A discussion of the various strategies schools have put in place to integrate struggling children, families, and communities is included. Issues arise in regard to how these programs will be funded, who is responsible for these children within schools, and recommendations going forward. School boards need to be allocated more funding and support from macro level institutions such as the government and health boards if they hope to find a solution.
Keywords: children; low socioeconomic status; schools